RANCANG BANGUN SISTEM PENERIMAAN DOKUMEN PADA PT. REASURANSI INDONESIA UTAMA - Dimas Indra Andhika; Muhammad Muharrom; Edhi Prayitno; Juarni Siregar (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2022)
In the Administration at PT. Reinsurance Indonesia Utama letter is an important means of important and confidential information related to the agency contained in it. Timeliness in receiving letters must be carried out quickly and precisely. Because of that, a better and structured mail receipt information system process is needed to be faster in searching for existing data and in the process of making reports. This letter receipt system has the following capabilities: This reception system is run on a computer operational network in the administration section of PT. Reinsurance Indonesia Utama, administrative officers can access the system by entering the correct admin login, can change, search, and save the letter. The research methods used are observation, interviews, literature studies, systems analysis, proposed system design, system testing, and system implementation. The result of this design is to produce an application that can manage letters according to the specified flow, and solve existing problems.